Risk of cerebrovascular events in persons with and without HIV: a Danish nationwide population-based cohort study - Rasmussen, Line D; Engsig, Frederik N; Christensen, Hanne; Gerstoft, Jan; Kronborg, Gitte; Pedersen, Court; Obel, Niels (AIDS (London), 2011)
To assess the risk of cerebrovascular events (CVEs) in HIV-infected individuals and evaluate the impact of proven risk factors, injection drug abuse (IDU), immunodeficiency, HAART and family-related risk factors. Nationwide, population-based cohort study. The study population included all Danish HIV-infected individuals, a population-based comparison cohort and parents of both cohorts - all with no prior cerebral comorbidity. We computed incidence rate ratios (IRRs) of overall CVEs and CVEs with and without proven risk factors, stratifying the analyses on IDU. Impact of immunodeficiency, HAART, protease inhibitors, indinavir, didanosin, tenofovir and abacavir on risk of CVEs was analyzed using time-dependent Cox regression analyses. HIV-infected individuals had an increased risk of CVEs compared with the comparison cohorts [(non-IDU HIV adjusted IRR 1.60; 95% confidence interval [CI] 1.32-1.94), (IDU HIV adjusted IRR 3.94; 95% CI 2.16-7.16)]. The risk was increased with and without proven risk factors. A CD4 cell count of 200 cells/μl or less before the start of HAART and exposure to abacavir increased the risk of CVE [(adjusted IRR 2.26; 95% CI 1.05-4.86) and (adjusted IRR 1.66; 95% CI 1.03-2.68)]. Protease inhibitors, indinavir, didanosin, tenofovir and HAART in general had no impact. Risk of CVEs was only increased in the parents of IDU HIV-infected individuals. HIV-infected individuals have an increased risk of CVEs with and without proven risk factors. The risk is associated with IDU, low CD4 cell count and exposure to abacavir, but not with HAART. An association with family-related risk factors seems vague except for parents of IDU individuals.